2012
DOI: 10.1016/j.ijporl.2012.02.039
|View full text |Cite
|
Sign up to set email alerts
|

Development of an adaptive low-pass filtered speech test for the identification of auditory processing disorders

Abstract: Objective: One type of test commonly used to examine auditory processing disorders (APD) is the low-pass filtered speech test (LPFST), of which there are various versions. In LPFSTs, a monaural, low-redundancy speech sample is distorted by using filtering to modify its frequency content. Due to the richness of the neural pathways in the auditory system and the redundancy of acoustic information in spoken language, a normal listener is able to recognize speech even when parts of the signal are missing, whereas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 23 publications
1
15
0
Order By: Relevance
“…This may be most relevant in the case of LPFS, as the filters applied to the stimuli on Willeford's version of the test tend to vary quite a bit from other versions of LPFS tests. In addition, some recent studies of children's performance on LPFS measures have suggested that adaptive LPFS tests that look at how much redundancy is needed to achieve a certain percent correct criterion may be a better indicator of monaural low redundancy deficits (O'Beirne et al, 2012;Rickard et al, 2013). Specifically, these studies have shown that children with central auditory processing issues tend to require a low-pass filter setting that is higher in frequency to achieve criterion when compared with children without deficits.…”
Section: Limitationsmentioning
confidence: 99%
“…This may be most relevant in the case of LPFS, as the filters applied to the stimuli on Willeford's version of the test tend to vary quite a bit from other versions of LPFS tests. In addition, some recent studies of children's performance on LPFS measures have suggested that adaptive LPFS tests that look at how much redundancy is needed to achieve a certain percent correct criterion may be a better indicator of monaural low redundancy deficits (O'Beirne et al, 2012;Rickard et al, 2013). Specifically, these studies have shown that children with central auditory processing issues tend to require a low-pass filter setting that is higher in frequency to achieve criterion when compared with children without deficits.…”
Section: Limitationsmentioning
confidence: 99%
“…In practice, the vast majority of clinical tests of AP are nonadaptive and assess performance at a single level of difficulty only. Thus, the ability of such tests to optimally engage a participant and to avoid effects of fatigue, boredom or discouragement depends on the difficulty level chosen by the developers of the test and on the homogeneity of test ability of the target population (O'Beirne et al, 2012). In an adaptive test, the level of difficulty of each trial is dependent on the participant's response to one or more previous trials (Leek, 2001).…”
Section: Tests Of Apmentioning
confidence: 99%
“…Filtering using a 500-Hz cut-off frequency with an 18 dB per octave rejection rate or a 1000 Hz cut-off has been recommended for clinical use (Wilson and Mueller, 1984). LPFS tests are available on the Veterans Administration compact disk (Veterans Administration, 1992), an Auditec of St. Louis recording (Wilson and Mueller, 1984), SCAN:3A and SCAN:3C (Keith, 2009a, b), and the University of Canterbury Adaptive Speech Test (O'Beirne et al, 2012). Stimuli are presented at 50 dB above the PTA (i.e., 50 dB SL re PTA).…”
Section: Low-pass Filtered Speech Testsmentioning
confidence: 99%